Clinical outcomes and safety of the SpineJack vertebral augmentation system for the treatment of vertebral compression fractures in a United States patient population. (July 2021) - England, Ryan W.; Gong, Anna; Li, Taibo; Botros, David; Manupipatpong, Sasicha; Pang, Sharon; Hui, Ferdinand; Khan, Majid
Highlights: The SpineJack implant system can be used to treat vertebral compression fractures. There is currently no SpineJack outcomes data for United States patients. Use of SpineJack is associated with decreased pain, without major adverse events. SpineJack implants restore vertebral height and improve local kyphotic angle. Abstract: The SpineJack implant system was recently FDA approved for treatment of vertebral compression fractures (VCF), however United States-based outcomes data is lacking. We sought to examine the safety and clinical outcomes following vertebral augmentation using the SpineJack implant for treatment of VCF in a U.S. patient population. An IRB-approved, retrospective study of SpineJack implants used in vertebral augmentation was performed from 11/2018 to 2/2020. Outcome objectives included pain improvement, vertebral body height (VH) restoration, improvement in local kyphotic angle (LKA), and incidence of adjacent level fractures (ALF). Complications were reviewed to assess safety of the procedure. Thirty patients with VCF (60% female; mean [SD] age of 62.7 [±12.8] years) underwent a total of 53 vertebral augmentations with 106 SpineJack implants. Worst pain scores decreased significantly from 8.7 to 4.3 (95%CI of the change [Δ]: 4.3–4.4; p < 0.001). Middle and anterior VH significantly increased from 13.1 ± 0.2 to 15.9 ± 0.2 mm (95%CI Δ: 2.6–2.9 mm; p < 0.001) and 15.6 ± 0.2 to 16.8 ± 0.2 mm (95%CI Δ: 1.1–1.4 mm; p < 0.001), respectively. LKA was significantly decreased from 10.0 ± 2.1 to 7.4 ± 2.1 degrees (95%CI Δ: 2.4–2.8 degrees; p < 0.001). Four patients (13%) sustained ten ALF over a median (IQR) follow up period of 94 (17.5–203) days. There were no major adverse events during the follow up period. To summarize, vertebral augmentation with SpineJack implants of patients with VCF resulted in significantly decreased pain, restored VH, and improved LKA, without major adverse events. However, 13% of patients sustained ALF during a median follow up period of 3 months.